Credit Constraints, Productivity Shocks and Consumption Volatility in Emerging Economies - Bhattacharya, Rudrani (IMF Working Papers; Working Paper ;, 2013)
How does access to credit impact consumption volatility? Theory and evidence from advanced economies suggests that greater household access to finance smooths consumption. Evidence from emerging markets, where consumption is usually more volatile than income, indicates that financial reform further increases the volatility of consumption relative to output. We address this puzzle in the framework of an emerging economy model in which households face shocks to trend growth rate, and a fraction of them are credit constrained. Unconstrained households can respond to shocks to trend growth by raising current consumption more than rise in current income. Financial reform increases the share of such households, leading to greater relative consumption volatility. Calibration of the model for pre and post financial reform in India provides support for the model's key predictions.